Association of De Novo Variants With Childhood Onset Moyamoya Disease and Diffuse Occlusive Vasculopathy. - Pinard, Amelie; Fiander, Maximillian D J; Cecchi, Alana C; Rideout, Andrea L; Azouz, Mohamed; Fraser, Stuart M; McNeely, P Daniel; Walling, Simon; Novara, Sarah C; Hurst, Anna C E; Guo, Dongchuan; Parkash, Sandhya; et al. (Neurology, 2021)
OBJECTIVE: To test the hypothesis that de novo genetic variants are responsible for moyamoya disease (MMD) in children with unaffected relatives, we performed exome sequencing of 28 affected children and their unaffected parents. METHODS: Exome sequencing was performed on 28 trios of affected patients with MMD and unaffected parents. RESULTS: We identified 3 novel rare de novo variants, 1 in the RING domain and 2 in a highly conserved region distal to the RING domain (4,114-4,120). These de novo cases of MMD present at a young age with aggressive MMD and uniquely have additional occlusive vascular lesions, including renal artery stenosis. Two previously reported cases had de novo variants in the same limited region and presented young with aggressive MMD, and 1 case had narrowing of the inferior abdominal aorta. CONCLUSIONS: These results indicate a novel syndrome associated with rare variants defined by de novo mutations disrupting highly conserved amino acids in the RING domain and a discrete region distal to the RING domain delimited by amino acids 4,114 to 4,120 leading to onset of severe MMD before 3 years of age and occlusion of other arteries, including the abdominal aorta, renal, iliac, and femoral arteries.
Keywords: Adenosine Triphosphatases; Adult; Age of Onset; Aortic Diseases; Arterial Occlusive Diseases; Child, Preschool; Female; Femoral Artery; Humans; Iliac Artery; Male; Moyamoya Disease; Mutation; Renal Artery Obstruction; Ubiquitin-Protein Ligases

The pleiotropy associated with de novo variants in CHD4, CNOT3, and SETD5 extends to moyamoya angiopathy. - Pinard, Amelie; Guey, Stéphanie; Guo, Dongchuan; Cecchi, Alana C; Kharas, Natasha; Wallace, Stephanie; Regalado, Ellen S; Hostetler, Ellen M; Sharrief, Anjail Z; Bergametti, Françoise; Kossorotoff, Manoelle; Hervé, Dominique; et al. (Genet Med, 2020)
PURPOSE: Moyamoya angiopathy (MMA) is a cerebrovascular disease characterized by occlusion of large arteries, which leads to strokes starting in childhood. Twelve altered genes predispose to MMA but the majority of cases of European descent do not have an identified genetic trigger. METHODS: Exome sequencing from 39 trios were analyzed. RESULTS: We identified four de novo variants in three genes not previously associated with MMA: CHD4, CNOT3, and SETD5. Identification of additional rare variants in these genes in 158 unrelated MMA probands provided further support that rare pathogenic variants in CHD4 and CNOT3 predispose to MMA. Previous studies identified de novo variants in these genes in children with developmental disorders (DD), intellectual disability, and congenital heart disease. CONCLUSION: These genes encode proteins involved in chromatin remodeling, and taken together with previously reported genes leading to MMA-like cerebrovascular occlusive disease (YY1AP1, SMARCAL1), implicate disrupted chromatin remodeling as a molecular pathway predisposing to early onset, large artery occlusive cerebrovascular disease. Furthermore, these data expand the spectrum of phenotypic pleiotropy due to alterations of CHD4, CNOT3, and SETD5 beyond DD to later onset disease in the cerebrovascular arteries and emphasize the need to assess clinical complications into adulthood for genes associated with DD.
Keywords: Adult; Cell Cycle Proteins; Cerebrovascular Disorders; Child; Child, Preschool; Developmental Disabilities; DNA Helicases; Exome; Female; Genetic Predisposition to Disease; Humans; Intellectual Disability; Male; Methyltransferases; Mi-2 Nucleosome Remodeling and Deacetylase Complex; Middle Aged; Moyamoya Disease; Mutation; Nuclear Proteins; Transcription Factors; Whole Exome Sequencing

LTBP3 Pathogenic Variants Predispose Individuals to Thoracic Aortic Aneurysms and Dissections. - Guo, Dong-Chuan; Regalado, Ellen S; Pinard, Amelie; Chen, Jiyuan; Lee, Kwanghyuk; Rigelsky, Christina; Zilberberg, Lior; Hostetler, Ellen M; Aldred, Micheala; Wallace, Stephanie E; Prakash, Siddharth K; Leal, Suzanne M; et al. (Am J Hum Genet, 2018)
The major diseases affecting the thoracic aorta are aneurysms and acute dissections, and pathogenic variants in 11 genes are confirmed to lead to heritable thoracic aortic disease. However, many families in which multiple members have thoracic aortic disease do not have alterations in the known aortopathy genes. Genes highly expressed in the aorta were assessed for rare variants in exome sequencing data from such families, and compound rare heterozygous variants (p.Pro45Argfs25 and p.Glu750) in LTBP3 were identified in affected members of one family. A homozygous variant (p.Asn678_Gly681delinsThrCys) that introduces an additional cysteine into an epidermal growth factor (EGF)-like domain in the corresponding protein, latent TGF-β binding protein (LTBP-3), was identified in a second family. Individuals with compound heterozygous or homozygous variants in these families have aneurysms and dissections of the thoracic aorta, as well as aneurysms of the abdominal aorta and other arteries, along with dental abnormalities and short stature. Heterozygous carriers of the p.Asn678_Gly681delinsThrCys variant have later onset of thoracic aortic disease, as well as dental abnormalities. In these families, LTBP3 variants segregated with thoracic aortic disease with a combined LOD score of 3.9. Additionally, heterozygous rare LTBP3 variants were found in individuals with early onset of acute aortic dissections, and some of these variants disrupted LTBP-3 levels or EGF-like domains. When compared to wild-type mice, Ltbp3 mice have enlarged aortic roots and ascending aortas. In summary, homozygous LTBP3 pathogenic variants predispose individuals to thoracic aortic aneurysms and dissections, along with the previously described skeletal and dental abnormalities.
Keywords: Adult; Aged, 80 and over; Aneurysm, Dissecting; Animals; Aortic Aneurysm, Thoracic; Blood Pressure; Female; Genetic Predisposition to Disease; Homozygote; Humans; Latent TGF-beta Binding Proteins; Male; Mice; Middle Aged; Mutation; Pedigree